コウクウ シャシン ニヨル アデリーペンギン ノ コタイスウ チョウサ ノ ココロミ ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 西脇, 三郎; ニシワキ, サブロウ; NISHIWAKI, Saburo (国立極地研究所, 1972)
P(論文) Aerophotography was applied in an attempt to count the number of Adelie penguins at the rookery on Rumpa Island near Syowa Station, Antarctica. The author first aimed at pursuing the fluctuations in the number of Adelie penguins at the rookery during their breeding season, but was unsuccessful, and only one each photograph of the two rookeries could be taken on February 14, 1971. Although the photographs obtained were not entirely satisfactory, a total number of 442 penguins were counted from the two photographs. On the basis of the present results, some considerations were given to the methods and possibility of the future application of aerophotography to the population study of Adelie penguins. departmental bulletin paper